2015
DOI: 10.1021/acs.jpcc.5b10799
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Disorder in Magnesium Aluminosilicate Glasses: Insights from 27Al and 17O NMR

Abstract: The quantification of the intrinsic disorder in archetypal noncrystalline magnesium aluminosilicates remains unsolved. This lack of knowledge is because of the increased structural perturbation caused by Mg2+, a high field strength cation, resulting in substantial broadening in both spectral and scattering responses. Most progress regarding amorphous aluminosilicate has thus been made with relatively low field strength cations (e.g., Na+ and Ca2+). Here, we quantified the nature of structural disorder in Mg-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 100 publications
(367 reference statements)
4
74
0
1
Order By: Relevance
“…Figure shows the 17 O 3QMAS NMR spectra of the Li–Ba silicate glasses; the Li–O–Si, {Li, Ba}–O–Si, Ba–O–Si, and Si–O–Si peaks are better resolved. The peak assignments of the BOs and NBOs in the 17 O 3QMAS NMR spectra are partially based on previous studies on crystalline and amorphous end‐member Li and Ba silicates . In 17 O 3QMAS NMR spectrum for Li 2 Si 2 O 5 glass, the Li–O–Si (~−29 ppm in the isotropic dimension, and ~31 ppm in the MAS dimension) and Si–O–Si (~−46 ppm in the isotropic dimension) are completely resolved.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure shows the 17 O 3QMAS NMR spectra of the Li–Ba silicate glasses; the Li–O–Si, {Li, Ba}–O–Si, Ba–O–Si, and Si–O–Si peaks are better resolved. The peak assignments of the BOs and NBOs in the 17 O 3QMAS NMR spectra are partially based on previous studies on crystalline and amorphous end‐member Li and Ba silicates . In 17 O 3QMAS NMR spectrum for Li 2 Si 2 O 5 glass, the Li–O–Si (~−29 ppm in the isotropic dimension, and ~31 ppm in the MAS dimension) and Si–O–Si (~−46 ppm in the isotropic dimension) are completely resolved.…”
Section: Resultsmentioning
confidence: 91%
“…While the preferential proximity between the network‐modifying cations and the diverse oxygen species (e.g., BOs and NBOs) is suggested to be controlled by the differences in nature of non‐network cations, the effects of the difference in the ionic radii on chemical ordering in mixed‐cation silicate glasses remain to be fully understood. Although previous studies on Ba–Mg (~0.63 Å) and K–Mg (~0.66 Å) silicate glasses may address the effect of the ionic radii on the degree of cation mixing, the observed nonrandomness in these glasses is attributable to the distinct nature of Mg 2+ (i.e., strong affinity between Mg 2+ and NBOs), rather than the difference in ionic radii on mixing between these cations . Thus, in order to establish the effects of the difference in the ionic radii on chemical ordering, study of other mixed‐cation silicate glasses with a larger difference in ionic radii has been anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Q = 0 indicates that Si and Al are randomly distributed within the unit structure. According to previous studies, the degree of aluminum avoidance ( Q ) varies with cation species (Ca 2+ : ~0.875, Mg 2+ : ~0.65, Li + : ~0.9, and Na + : ~0.95). Experimental studies have shown that Q ranges from 0.8 to 0.875 in the metaluminous join (XnormalCaO/XnormalAl2normalO3=1).…”
Section: Resultsmentioning
confidence: 95%
“…According to previous studies, 36,40 the degree of aluminum avoidance (Q) varies with cation species 40 (Ca 2+ :~0.875, Mg 2+ :~0.65, Li + :~0.9, and Na + :~0.95). Experimental studies 36,40 have shown that Q ranges from 0.8 to 0.875 in the metaluminous join (X CaO =X Al 2 O 3 ¼ 1). In this study, as the influence of composition on the range of Q was smaller than the cation effect, for convenience, the maximum value Q = 0.875 was employed in the model.…”
Section: Methodsmentioning
confidence: 93%
“…수행되었다. [13,14] 또한 Al-27 NMR 연구로부터 다성분계 비정 질 산화물 내의 구성양이온들의 세기(cation field strength)가 증가할수록 화학적 -위상학적 무질서도가 증가하고, 고배위수 Al( [5] Al, [6] Al)의 양이 증가하는 것을 정량 적으로 확인하였다. Al, [5] Al, [6] Al)이 관찰된다.…”
unclassified